Mothers-Grandmothers. Notes on the historical making of the Grandmothers of the Plaza de Mayo - Laino Sanchis, Fabricio Andrés (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
In this article we will address the historical formation process of Abuelas de Plaza de Mayo. We will reconstruct the origins of the original nucleus of “mothers-grandmothers” as a “sub-commission of grandmothers” within Madres de Plaza de Mayo. We will analyze the different alternatives that arose along the way and the factors that contributed to the progressive autonomization of the group and its final transformation into an independent group specifically dedicated to the cause of the restitution of the “disappeared children” which, in turn, managed to transform this claim into a public problem in the national (and, to a certain extent, international) public sphere. We will also look at other collective action initiatives that were synchronous with (or even preceded) the formation of Abuelas, both in the Buenos Aires metropolitan region and in other parts of the country. Although these initiatives were not sustained over time, they will allow us to observe the contingent and processual character of the formation of Abuelas as the main (and almost exclusive) referent in the search for the “disappeared children”.